Fungi Associated With Woody Tissues of European Beech and Their Impact on Tree Health - Langer, Gitta Jutta; Bußkamp, Johanna (Frontiers in Microbiology, 2021)
Filamentous fungi associated with woody tissues of European Beech (Fagus sylvatica) and isolated from diseased trees and healthy trees were examined in relation to their impact on tree health. To this end, classical culture-based isolation methods, in planta inoculations and fungal identification using ITS-barcode and morphological characters were used. Stem endophytes of healthy beech saplings collected in German forests were isolated to determine endophyte communities in woody stem tissues. Pathogenicity tests were performed on living potted beech saplings using twelve selected fungal pathogens and wood inhabiting fungi (Hypocreales, Botryosphaeriales, and Xylariales) originating mainly from European beech with symptoms of the complex disease Vitality loss, or from bark necroses, or known to be common endophytes of beech. The impact of these ascomycetous fungi with respect to tree health was discussed. The potential influences of endophytic fungi of beech and of test conditions are discussed in relation to the success of inoculation. All tested fungal strains except for Neonectria ditissima were able to establish themselves post inoculation in the beech stems and caused necroses when there was sufficient water, but at different severities. Under the experimental conditions, Botryosphaeria corticola was shown to be the most virulent tested latent pathogen against F. sylvatica. In the context of climate change and global warming, the tested Botryosphaeriaceae are able to play a primary role in the disease progress of Vitality loss of Beech. The key role of Neonectria coccinea in causing bark necroses and the loss of vitality in beech was confirmed because the tested strain induced large lesions on the beech saplings.